2013
DOI: 10.5586/asbp.2013.034
|View full text |Cite
|
Sign up to set email alerts
|

A new and fast method to obtain in vitro cultures of Huperzia selago (Huperziaceae) sporophytes, a club moss which is a source of huperzine A

Abstract: This study presents a protocol for a fast and effective in vitro axenic culture of <em>Huperzia selago</em> (Huperziaceae Rothm.) sporophytes, a club moss which is a source of huperzine A, an alkaloid of a considerable therapeutic potential extensively investigated for its uses as treatment for some neurodegenerative diseases. The proposed procedure allowed approximately tenfold shortening of the species developmental stages with the omission of the gametophyte stage while the sporophyte mass could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…As demonstrated in the present study, the use of MS medium rich in reduced nitrogen produced the least increase in biomass growth. Similarly, MS medium proved not suitable for sporophyte cultures [25]. The fastest gametophyte biomass growth was observed on W/S media without growth regulators.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…As demonstrated in the present study, the use of MS medium rich in reduced nitrogen produced the least increase in biomass growth. Similarly, MS medium proved not suitable for sporophyte cultures [25]. The fastest gametophyte biomass growth was observed on W/S media without growth regulators.…”
Section: Discussionmentioning
confidence: 96%
“…Up to now, club moss gametophytes from natural populations have been only infrequently described and in very rare cases they were obtained in vitro, but they have not been effectively used for the biosynthesis of secondary metabolites [23]. The first studies on the biosynthesis of HupA were conducted by Szypuła et al [17,20,25] and Ma and Gang [24]. Szypuła et al [17] presented a protocol for the establishment and maintenance of in vitro culture of Huperzia selago sporophytes from shoot explants (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, studies by Szypuła et al [46][47][48] have shown that H. selago is a rich source of HupA and other alkaloids, which are much more abundant in this plant than in the Chinese club moss H. serrata.…”
Section: Introductionmentioning
confidence: 99%